2018
DOI: 10.1007/s00403-018-1851-7
|View full text |Cite
|
Sign up to set email alerts
|

Different Trypanosoma cruzi calreticulin domains mediate migration and proliferation of fibroblasts in vitro and skin wound healing in vivo

Abstract: Calreticulin is an endoplasmic reticulum-resident, calcium-binding, stress-produced, chaperone protein that serves multiple functions and is widely distributed in eukaryotic cells. Exogenously applied recombinant calreticulin solution, markedly enhanced the rate and quality of skin wound healing. These modulatory effects are more efficient than commercially available topic platelet-derived growth factor ointments (Regranex). Trypanosoma cruzi calreticulin is more effective in equimolar terms to human counterpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In summary, a greater amount of granulation tissue replete with epidermal appendages was observed in the calreticulin treated excisional mouse wounds (right panels) compared to buffer‐treated controls (left panels). Although there might be subtle differences, the results observed are likely not female‐dependent as another study showed that treatment of male rats with Trypanosoma Cruzi CRT enhanced cutaneous wound healing 53 …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In summary, a greater amount of granulation tissue replete with epidermal appendages was observed in the calreticulin treated excisional mouse wounds (right panels) compared to buffer‐treated controls (left panels). Although there might be subtle differences, the results observed are likely not female‐dependent as another study showed that treatment of male rats with Trypanosoma Cruzi CRT enhanced cutaneous wound healing 53 …”
Section: Resultsmentioning
confidence: 93%
“…Although there might be subtle differences, the results observed are likely not female-dependent as another study showed that treatment of male rats with Trypanosoma Cruzi CRT enhanced cutaneous wound healing. 53…”
Section: Hff 24hmentioning
confidence: 99%
“…Calr is important in the wound healing process. rTcCalr has been shown to be more effective than HsCalr in this setting, requiring lower concentrations to promote proliferation of fibroblasts, migration of epithelial cells and formation of granulation tissue ( 13 , 148 ). Interestingly, these effects were only observed when the whole protein was administered, suggesting that the protein in its entirety or a large fragment of it is necessary to promote re-epitelization ( 148 ).…”
Section: Calreticulin In Wound Healing and Autoimmunitymentioning
confidence: 99%
“…These cells can be engulfed by macrophages and dendritic cells co-cultured with rTcCalr, accelerating its maturation and activating T cells ( 100 ). Similar to its human counterpart, TcCalr promotes wound healing in rats ( 101 ); however, whether this property correlates with the known anti-complement capacity of the parasite chaperone, is unknown.…”
Section: Other Tccalr Functions In the Host-parasite Interplaymentioning
confidence: 99%